Collaborative School-Family Relationships using the Expansive Learning Cycle to Enhance Parents Empowering in Helping their Child in the Context of a New Reading Method - Deslandes, Rollande; Barma, Sylvie; Beaumier, France (International Journal about Parents in Education, 2023)
The benefits of parental involvement in literacy have been well documented over the years. It has also been shown that when introducing new ways of doing things, parents often show resistance. It is with a view to improving school-family collaboration in the context of La Planète des Alphas, a new reading method, that we conducted a research-intervention. This paper aims to describe how teachers question their own practices and interact with parents to give help and to put forward new models of pedagogical actions. This research-intervention employed the Cultural-Historical Activity Theory and the Change Laboratory methodology. We take a close look at the evolution of the discursive manifestations of transformative agency during the Change Laboratory sessions and the discussion topics they were related to. This approach deepens our understanding of the decision making process in the selection of new solutions and the notion of relational agency in fostering collaboration and communication throughout the expansive learning cycle. Five Change Laboratory sessions were coded and analyzed using MAXQDA 2018 software. We highlight the activity system boundary crossing that allowed teachers, parents and school principal to elaborate, implement and reflect upon new instrument- producing activities aiming at empowering parents in helping their child in schooling. Obviously, the relevance of this intervention and research process can be well extended to the overall field language construction and the overall literature on family-school relationships.